Biogas reforming for hydrogen-rich syngas production over a Ni–K/Al2O3 catalyst using a temperature-controlled plasma reactor. (22nd February 2023) - Zeng, Yuxuan; Chen, Guoxing; Bai, Qianyun; Wang, Li; Wu, Renbing; Tu, Xin
Abstract: Plasma-enhanced catalytic biogas reforming for hydrogen-rich syngas production over a Ni–K/Al2 O3 catalyst was investigated using a tabular dielectric barrier discharge non-thermal plasma reactor. To better understand the plasma catalysis synergy at elevated temperatures, we compared different reaction modes: plasma catalysis, plasma alone, and catalysis alone in a reaction temperature range of 160–400 °C. The combination of Ni–K/Al2 O3 and plasma produced synergistic effects. Notably, the plasma-catalytic synergy was temperature-dependent and varied at different reaction temperatures. Using plasma catalysis, the maximum conversion of CH4 and CO2 (31.6% and 22.8%, respectively) was attained over Ni–K/Al2 O3 at 160 °C, while increasing the reaction temperature to 340 °C noticeably enhanced the H2 /CO ratio to 2.71. Moreover, compared to plasma-catalytic biogas reforming at 160 °C, increasing the reaction temperature to 400 °C suppressed biogas conversion with dramatically reduced coke formation on the Ni–K/Al2 O3 surface from 6.81 wt% to 3.37 wt%. Highlights: Plasma-catalytic biogas reforming over a Ni–K/Al2 O3 catalyst was carried out. The effect of reaction temperature on biogas reforming was evaluated. The plasma-catalytic synergy recorded a temperature-dependent behavior. The highest CO2 and CH4 conversion was achieved using plasma catalysis at 160 °C. Increasing the reaction temperature to 400 °C reduced the conversion of biogas.